Single-cell sequencing reveals cellular heterogeneity and molecular mechanisms in tendon and enthesis injury repair - Pan, Tingming; Dong, Zhong; Zhang, Hongjie; Yang, Fengmin; Chen, Yating (Frontiers in Physiology, 2025)
BackgroundTendon and enthesis injuries represent a significant global health challenge, severely impairing patient mobility and self-care abilities while imposing substantial medical burdens.Main BodyPoor clinical outcomes in tendon healing stem from the complex enthesis, which involves diverse cell types and signaling pathways. Recent advances in single-cell sequencing technologies have revealed detailed cellular diversity and function in tendon and tendon-bone healing. Using multimodal integration, researchers have identified precise subpopulations of tendon and enthesis cells. They have also clarified cell-to-cell crosstalk and mapped differentiation paths during healing.ConclusionThese new findings, guided by emerging methodological advancements. They offer innovative perspectives for developing targeted clinical interventions for tendon and enthesis injury.